Pendampingan Baca Qur’an Menggunakan Metode Dirosa Pada Majelis Ta’lim Al-Miftahusahada Topisi - Suriyati, Suriyati; suriati, suriati; Anis, Muh.; Riska, Riska; Iftika, Nur (INKAMKU : Journal of Community Service, 2024)
The aim of this service is to determine the level of proficiency of the mothers at the al-Miftahusahada Topisi Ta'lim Council in reading the al-Qur'an based on the rules of Tajwid science. However, a phenomenon that often occurs is that many individuals experience illiteracy in the Koran, so it requires our collective efforts to overcome this problem. The method used in this assistance is the Dirosa method. This service is carried out by inviting mothers to study and test the al-Qur'an reading skills of the women from the Ta'lim Council. The benefit of this service is that we can understand mentoring. This Dirosa method is very important because it can reveal that the al-Qur'an is the main source of Islamic teachings and guidance for all mankind. In this case, to help mothers learn to read the al-Qur'an through the Dirosa method, which is structured in a creative and innovative form of learning, such as reading the al-Qur'an according to Tajwid, enabling mothers to know more about reading al-Qur'an. -The Qur'an properly and correctly and foster a deep love for the Qur'an. The results of observations of this service through pre-test and post-test showed that there were 7 people who did not know letters or were illiterate, 8 people who could not connect letters and 10 people who were able to read but did not comply with Tajwid science. The conclusion from the implementation of this activity, namely using the Dirosa method, shows that out of 25 participants, 9 people can read the Koran fluently and 16 people know the letters well and regularly. Recite according to the rules. Through this service, it is hoped that it can attract the attention of parents by motivating children to study the Koran more actively